The Indonesian Vocabulary Enrichment through Arabic - Suparman, Tatang; Suganda, Dadang; Wahya (International Journal of Psychosocial Rehabilitation, 2020)
There are two major theories in the treatment of a vocabulary that is enriched from other languages. First, a vocabulary word must be given the form and meaning of the original language. The second theory states that the vocabulary of levies from other languages no longer has to be in accordance with the form and meaning of the original language. Writing with the title "Enrichment of Indonesian Vocabulary through Arabic: Religious List" examines the vocabulary instructions for these theories in the perspective of the Islamic religion. The title of this paper is part of the author’s research dissertation with the title "Indonesian Language Vocabulary Enrichment". The purpose of this study is to get a clear picture of the enrichment of English from Arabic in the list of religions. Indonesian from Arabic which is used in Islammany that deviate from the original meaning requires a formula to overcome it in the language that is translated by transcribing the Arabic letters into Latin-Indonesian letters. The method used is descriptive method - a method that describes the process and results of research with what is there. How does the technique remember by direct notes?. The enrichment of foreign vocabulary into Indonesian is noticed its etymology so that the word absorbed matches the original meaning and exists which no longer matches the meaning of the original word. 2. The enrichment of Indonesian vocabulary from Arabic in Islam many whose meanings are not in accordance with the original word meaning (Arabic), giving rise to distorted meanings. The current research provide a clear picture of the enrichment of English from Arabic in the list of religions.